New challenges for higher education: self-regulated learning in blended learning contexts - Lobos, Karla; Cobo-Rendón, Rubia; Bruna Jofré, Daniela; Santana, Javiera (Frontiers in Education, 2024)
The study on self-regulated learning in blended learning (BL) environments highlights its crucial relevance for both the academic development of students and the evolution of contemporary educational methods. This research focused on conceptualizing self-regulated learning in university contexts with a B-L modality, using direct student perceptions. An inductive qualitative approach with a phenomenological design was employed. Responses from 312 undergraduate students who had completed their first or second year were analyzed; 65 participated in 10 focus groups (two focus groups per area of knowledge according to OECD classification) and 247 participated through a survey. Through descriptive analysis, a range of content and meanings associated with students' perceptions of SRL-BL was obtained. The study conceptualized SRL-BL as a process where students structure, monitor, and evaluate their learning using self-reflection and digital technologies, with particular emphasis on planning. Significant differences were identified between SRL-BL and traditional SRL; in face-to-face education, teacher supervision is greater, while in SRL-BL, students take on more responsibility and autonomy, developing self-management skills. Although SRL-BL fosters autonomy and responsibility, students face obstacles such as distractions from social media and leisure technologies, which affect their concentration and study planning. It is essential to address the new challenges students face to maintain a high level of SRL in Blended Learning environments (SRL-BL) and the strategies they use to overcome them. The need to update the concept of self-regulated learning (SRL) in the current educational context, influenced by technological advances, is concluded.